Composite steel core ferronickel welding rod and preparation method thereof
By adopting a composite steel core and coated powder design in nickel-iron welding rod, the problem of the powder skin prone to cracking and falling off during welding is solved, and efficient welding and stable welding performance is achieved, reducing resource waste.
Patent Information
- Application Number
- CN202411939061.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-26
AI Technical Summary
Existing nickel-iron welding rods are prone to cracking and falling off the skin during welding, resulting in poor welding or waste of resources, affecting work efficiency.
The composite steel core nickel-iron welding rod is used. The welding core is wrapped inside the low-carbon steel belt, and the medicine skin is wrapped outside the steel belt. The components of the medicine skin include marble, fluorite, barium carbonate, iron powder, graphite, nickel powder, manganese metal, atomized ferrosilicon, feldspar, soda ash, CMC and microcrystalline cellulose. They are evenly mixed by stirring and press-coated on the welding rod and dried.
It effectively avoids the redness and heat problems of welding rods during welding and cracking and shedding of the medicine skin, and realizes high-efficiency welding of ultra-large current, reduces resource waste, and has stable welding process and mechanical properties.
Smart Images

Figure CN119635082A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of welding materials, and particularly relates to a composite steel core nickel-iron welding rod and a preparation method thereof. Background Art
[0002] Nickel-iron welding rods can be used in mechanical equipment, wear-resistant repair, special material welding and other scenarios due to their high strength, low stress, good adaptability and all-position welding characteristics. For example, in the welding and repair of various cast irons and their deformed materials, they are used to weld cast irons and their deformed materials, including carbon steel, low alloy steel and nickel alloys. Currently, the commonly used nickel-iron welding rods have the problem of easy cracking and shedding of the coating during welding, and the latter half of the welding rod becomes red and hot. Usually, when welding to 1 / 2 of the entire welding rod, the latter section of the welding rod becomes red and hot, resulting in poor welding or being directly discarded, causing great waste of resources and seriously affecting work efficiency. Summary of the invention
[0003] In view of the above problems existing in the prior art, the present invention provides a composite steel core nickel-iron welding rod and a preparation method thereof, so as to improve the problem that the coating of the existing nickel-iron welding rod is easy to crack and fall off, improve the utilization rate of the welding rod, and improve work efficiency.
[0004] To achieve the above-mentioned purpose and other related purposes, the first aspect of the present invention provides a composite steel core nickel-iron welding rod, which comprises a welding core, a steel strip and a coating, wherein the welding core is wrapped inside the steel strip, and the coating is coated outside the steel strip, wherein the coating comprises the following components and the weight proportions of each component are respectively: 32 to 40 parts of marble, 18 to 23 parts of fluorite, 10 to 15 parts of barium carbonate, 5 to 10 parts of iron powder, 4 to 7 parts of graphite, 3 to 10 parts of nickel powder, 1 to 3 parts of metallic manganese, 3 to 5 parts of atomized ferrosilicon, 2 to 4 parts of feldspar, 0.5 to 1 part of soda ash, 0.3 to 0.5 parts of CMC, and 0.3 to 0.8 parts of microcrystalline cellulose; in terms of the mass percentage of the welding core, the welding core comprises the following components and the content of each component is: nickel content ≥99wt%, and the balance is unavoidable impurities.
[0005] In one example of the present invention, the steel strip is a low-carbon steel strip, and the steel strip includes the following components and the weight percentage of each component is: C≤0.05%, Mn≤0.35%, Si≤0.1%, S≤0.03%, P≤0.03%, and the rest is Fe and unavoidable impurities.
[0006] In an example of the present invention, the weight of the welding core is 45-55% of the total weight of the welding core and the steel strip.
[0007] In an example of the present invention, the weight of the welding core and the steel strip is 50-60% of the total mass of the composite steel core nickel-iron welding rod.
[0008] A second aspect of the present invention provides a method for preparing a composite steel core nickel-iron welding rod, comprising the following steps:
[0009] Cut the steel strip to the required width and roll it into a U-shape using a rolling mill;
[0010] The welding core is placed inside the U-shaped steel strip, the U-shaped composite steel core with the welding core is joined into a circle, and the composite steel core is drawn to obtain the composite steel core;
[0011] The components of the drug coating are sieved and weighed respectively to obtain drug coating powder;
[0012] Add the coating powder into a mixer, add a binder into the mixer, and stir and mix evenly to obtain a coating mixed powder;
[0013] The coating mixed powder is pressed onto the composite steel core, and after drying, a composite steel core nickel-iron welding rod is obtained.
[0014] In one example of the present invention, the binder is a water glass binder, and the added amount of the binder is 21-23% of the coating powder.
[0015] In an example of the present invention, the diameter of the composite steel core is 2.5-5.0 mm.
[0016] In one example of the present invention, marble, fluorite, nickel powder, iron powder, metallic manganese, atomized ferrosilicon, and feldspar are sieved through a 40-mesh sieve, microcrystalline cellulose is sieved through a 120-mesh sieve, and barium carbonate and soda ash are sieved through an 80-mesh sieve.
[0017] In an example of the present invention, the drying temperature is 280-300° C., and the drying time is 1-2 hours.
[0018] The composite steel core nickel-iron welding rod of the present application wraps the steel strip around the outside of the welding core and coats the outside of the steel strip with a coating. The welding core is made of metal nickel and the steel strip is made of low-carbon steel. The resistivity of low-carbon steel is low and the expansion phenomenon is not obvious. The welding rod does not have the problem of redness and heating during welding, and the coating does not have the problem of cracking or falling off. It can achieve ultra-large current and efficient welding and reduce waste. At the same time, the welding processability and mechanical properties of the welding rod of the present application are stable. Due to the improved conductivity of the welding rod, the welding rod combustion is more stable, the molten droplet transition is more uniform and stable, and the weld performance is more stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.
[0020] Figure 1 The present invention is a flow chart of the preparation of the composite steel core nickel-iron welding rod in one embodiment. DETAILED DESCRIPTION
[0021] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.
[0022] When numerical ranges are given in the embodiments, it should be understood that unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any method, device and material of the prior art similar or equivalent to the method, device and material in the embodiments of the present invention can also be used to implement the present invention.
[0023] It should be noted that the terms such as "upper", "lower", "left", "right", "middle" and "one" etc. used in this specification are only for the convenience of description and are not intended to limit the scope of implementation of the present invention. Changes or adjustments to their relative relationships, without substantially changing the technical content, should also be regarded as the scope of implementation of the present invention.
[0024] It should be noted that "%" and "wt%" in this specification represent mass percentage, and "part" represents part by weight.
[0025] The invention provides a composite steel core nickel-iron welding rod. The composite steel core nickel-iron welding rod comprises a welding core, a steel strip and a coating, wherein the welding core is wrapped inside the steel strip, and the coating is coated outside the steel strip. The invention is characterized in that the coating comprises the following components and the weight proportions of the components are respectively: 32-40 parts of marble, 18-23 parts of fluorite, 10-15 parts of barium carbonate, 5-10 parts of iron powder, 4-7 parts of graphite, 3-10 parts of nickel powder, 1-3 parts of metallic manganese, 3-5 parts of atomized ferrosilicon, 2-4 parts of feldspar, 0.5-1 part of soda ash, 0.3-0.5 part of CMC and 0.3-0.8 part of microcrystalline cellulose; in terms of the mass percentage of the welding core, the welding core comprises the following components and the content of the components is: the nickel content is ≥99wt%, and the balance is inevitable impurities.
[0026] In one embodiment, the steel strip is a low-carbon steel strip, and the steel strip includes the following components and the weight percentage of each component is: C≤0.05%, Mn≤0.35%, Si≤0.1%, S≤0.03%, P≤0.03%, and the rest is Fe and unavoidable impurities.
[0027] In one embodiment, the weight of the welding core is 45-55% of the total weight of the welding core and the steel strip.
[0028] In one embodiment, the weight of the welding core and the steel strip is 50-60% of the total weight of the composite steel core nickel-iron welding rod.
[0029] In this application, the functions of the components in the drug cover are as follows:
[0030] Metallic manganese: Mainly used as a deoxidizer, alloying agent and desulfurizer, it transfers the Mn element to the weld to improve the weld strength.
[0031] Atomized ferrosilicon: Mainly used as a deoxidizer and alloying agent. Adding too much will increase spatter and reduce toughness, while adding too little will lead to poor fluidity of the molten pool and poor mechanical properties of the weld.
[0032] Nickel powder: Mainly used for alloying, to adjust the nickel content of the electrode deposited metal, so that the weld has better crack resistance and corrosion resistance.
[0033] Graphite: Its main function is to deoxidize and transfer carbon elements to the weld. Carbon helps to reduce the formation of thermal cracks; the increase of carbon makes the volume shrinkage of the weld metal more uniform during the cooling process, reduces stress concentration, and thus reduces shrinkage stress. In addition, graphite can increase the slipperiness of the powder, improve the pressure coating performance of the electrode and the smoothness of the electrode surface.
[0034] Iron powder: regulates the chemical composition of the electrode deposited metal and stabilizes the performance of the electrode. Iron powder can also improve the arc state and regulate the fluidity of molten iron.
[0035] Marble: The main component is CaCO3, which has the function of gasification and slag formation. During welding, it decomposes to produce CO2 and CaO-based alkaline oxides. CO2 can protect the molten pool from air intrusion. CaO can increase the basicity of the slag, refine the molten droplets, and remove S and P, thereby improving the crack resistance of the weld metal. Too much addition will cause increased spatter, while too little addition will cause porosity defects in the product.
[0036] Fluorite: The main component is CaF2, which has the functions of slag formation, deoxidation and dehydrogenation. It can adjust the viscosity of slag and improve the fluidity of weld. The F element combines with the harmful element H to reduce the H content in the weld and purify the weld. Too much addition will lead to poor weld formation, and too little addition will easily cause porosity defects.
[0037] Mica and feldspar: the main arc stabilizers. The low-ionized substances they contain, such as K, Na and other elements, can effectively increase the stability of the arc. If too much is added, the amount of smoke will increase, and if too little is added, the arc stabilization effect will not be obvious.
[0038] The composite steel core nickel-iron welding rod of the present application does not have the problem of reddening and heating during welding, and the coating does not have the problem of cracking or falling off. It can realize ultra-large current and efficient welding, reduce waste, and has stable welding processability and mechanical properties. The welding rod combustion is more stable, the molten droplet transition is more uniform and stable, and the weld performance is more stable.
[0039] See also Figure 1 The present invention also provides a method for preparing a composite steel core nickel-iron welding rod, comprising the following steps:
[0040] S1. Cut the steel strip to the required width and roll it into a U-shape using a rolling mill;
[0041] S2, placing the welding core inside the U-shaped steel strip, joining the U-shaped composite steel core with the welding core into a circle, and drawing to obtain the composite steel core;
[0042] S3, sieving and weighing the components of the coating respectively to obtain coating powder;
[0043] S4, adding the coating powder into a mixer, adding a binder into the mixer, stirring and mixing evenly to obtain a coating mixed powder;
[0044] S5. Press-coat the mixed powder of the coating onto the composite steel core, and obtain the composite steel core nickel-iron welding rod after drying.
[0045] In step S1, the steel strip is a low-carbon steel strip, and the steel strip includes the following components and the weight percentage of each component is: C≤0.05%, Mn≤0.35%, Si≤0.1%, S≤0.03%, P≤0.03%, and the rest is Fe and unavoidable impurities.
[0046] In step S2, the welding core includes the following components and the content of each component is: nickel content ≥ 99wt%, and the balance is inevitable impurities. The diameter of the composite steel core is 2.5-5.0mm, for example, any value of 2.5mm, 3.0mm, 4.0mm or 5.0mm, etc.
[0047] In step S3, the coating includes the following components and the weight proportions of each component are: 32-40 parts of marble, 18-23 parts of fluorite, 10-15 parts of barium carbonate, 5-10 parts of iron powder, 4-7 parts of graphite, 3-10 parts of nickel powder, 1-3 parts of metal manganese, 3-5 parts of atomized ferrosilicon, 2-4 parts of feldspar, 0.5-1 part of soda ash, 0.3-0.5 parts of CMC, and 0.3-0.8 parts of microcrystalline cellulose. In one embodiment, marble, fluorite, nickel powder, iron powder, metal manganese, atomized ferrosilicon, and feldspar are sieved through a 40-mesh sieve, microcrystalline cellulose is sieved through a 120-mesh sieve, and barium carbonate and soda ash are sieved through an 80-mesh sieve.
[0048] In step S4, the binder is water glass binder, and the amount of the binder added is 21-23% of the coating powder, for example, any value within the range of 21%, 22% or 23%.
[0049] In step S5, the drying temperature is 280-300°C, for example, 280°C, 290°C, 300°C, or any other value within the range of 280-300°C, and the drying time is 1-2h, for example, 1h, 1.5h, 2h, or any other value within the range of 1-2h.
[0050] In the present application, the coating is stirred using a conventional stirring device and a conventional stirring method in the art, and the pressure coating uses a conventional pressure coating device and a conventional pressure coating method in the art, which will not be described in detail here.
[0051] The technical scheme of the present invention is described in detail below through several specific examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.
[0052] In the following examples, marble, fluorite, nickel powder, iron powder, metallic manganese, atomized ferrosilicon, and feldspar were sieved through a 40-mesh sieve, microcrystalline cellulose was sieved through a 120-mesh sieve, and barium carbonate and soda ash were sieved through an 80-mesh sieve.
[0053] Example 1
[0054] The composite steel core nickel-iron welding rod of this embodiment includes a welding core, a steel strip and a coating, wherein the welding core is wrapped inside the steel strip and the coating is coated outside the steel strip. The coating includes the following components and the weight proportions of each component are: 32 parts of marble, 18 parts of fluorite, 15 parts of barium carbonate, 5 parts of iron powder, 7 parts of graphite, 10 parts of nickel powder, 1 part of metallic manganese, 3 parts of atomized ferrosilicon, 2 parts of feldspar, 0.5 parts of soda ash, 0.3 parts of CMC, and 0.5 parts of microcrystalline cellulose. The nickel content in the welding core is 99.5wt%.
[0055] In this embodiment, the preparation method of the composite steel core nickel-iron welding rod is as follows: cut the steel strip to the required width and roll it into a U shape using a rolling mill; place the welding core inside the U-shaped steel strip, and sew the U-shaped composite steel core with the welding core into a circle, and draw to obtain the composite steel core; sieve the components of the coating separately and weigh them according to the above ratio to obtain the coating powder; add the coating powder to a blender, and add a binder to the blender, stir and mix evenly to obtain a coating mixed powder; press the coating mixed powder onto the composite steel core, and dry it at 280°C for 2 hours to obtain a composite steel core nickel-iron welding rod.
[0056] In this embodiment, the weight of the welding core is 45% of the weight of the composite steel core, the weight of the composite steel core is 50% of the total weight of the welding rod, the amount of binder added is 23% of the total weight of the coating powder, and the diameter of the composite steel core is 4.0 mm.
[0057] Example 2
[0058] The composite steel core nickel-iron welding rod of this embodiment includes a welding core, a steel strip and a coating, wherein the welding core is wrapped inside the steel strip and the coating is coated outside the steel strip. The coating includes the following components and the weight proportions of each component are: 36 parts of marble, 20 parts of fluorite, 10 parts of barium carbonate, 7 parts of iron powder, 5 parts of graphite, 7 parts of nickel powder, 2 parts of metallic manganese, 4 parts of atomized ferrosilicon, 3 parts of feldspar, 1 part of soda ash, 0.5 parts of CMC, and 0.8 parts of microcrystalline cellulose. The nickel content in the welding core is 99wt%.
[0059] In this embodiment, the preparation method of the composite steel core nickel-iron welding rod is as follows: cut the steel strip to the required width and roll it into a U shape using a rolling mill; place the welding core inside the U-shaped steel strip, sew the U-shaped composite steel core with the welding core into a circle, and draw to obtain the composite steel core; sieve the components of the coating separately and weigh them according to the above ratio to obtain the coating powder; add the coating powder to a blender, and add a binder to the blender, stir and mix evenly to obtain a coating mixed powder; press the coating mixed powder onto the composite steel core, and dry it at 300°C for 1 hour to obtain a composite steel core nickel-iron welding rod.
[0060] In this embodiment, the weight of the welding core is 50% of the weight of the composite steel core, the weight of the composite steel core is 60% of the total weight of the welding rod, the amount of binder added is 22% of the total weight of the coating powder, and the diameter of the composite steel core is 3.2 mm.
[0061] Example 3
[0062] The composite steel core nickel-iron welding rod of this embodiment includes a welding core, a steel strip and a coating, wherein the welding core is wrapped inside the steel strip and the coating is coated outside the steel strip. The coating includes the following components and the weight proportions of each component are: 40 parts of marble, 22 parts of fluorite, 11 parts of barium carbonate, 10 parts of iron powder, 4 parts of graphite, 3 parts of nickel powder, 3 parts of metallic manganese, 5 parts of atomized ferrosilicon, 4 parts of feldspar, 0.8 parts of soda ash, 0.4 parts of CMC, and 0.6 parts of microcrystalline cellulose. The nickel content in the welding core is 99.5wt%.
[0063] In this embodiment, the preparation method of the composite steel core nickel-iron welding rod is as follows: cut the steel strip to the required width and roll it into a U shape using a rolling mill; place the welding core inside the U-shaped steel strip, and sew the U-shaped composite steel core with the welding core into a circle, and draw to obtain the composite steel core; sieve the components of the coating separately and weigh them according to the above ratio to obtain the coating powder; add the coating powder to a blender, and add a binder to the blender, stir and mix evenly to obtain a coating mixed powder; press the coating mixed powder onto the composite steel core, and dry it at 290°C for 1 hour to obtain a composite steel core nickel-iron welding rod.
[0064] In this embodiment, the weight of the welding core is 55% of the weight of the composite steel core, the weight of the composite steel core is 53% of the total weight of the welding rod, the amount of binder added is 21% of the total weight of the coating powder, and the diameter of the composite steel core is 2.5 mm.
[0065] Example 4
[0066] The composite steel core nickel-iron welding rod of this embodiment includes a welding core, a steel strip and a coating, wherein the welding core is wrapped inside the steel strip and the coating is coated outside the steel strip. The coating includes the following components and the weight proportions of each component are: 38 parts of marble, 23 parts of fluorite, 12 parts of barium carbonate, 8 parts of iron powder, 6 parts of graphite, 5 parts of nickel powder, 1.5 parts of metallic manganese, 3.5 parts of atomized ferrosilicon, 2.5 parts of feldspar, 0.6 parts of soda ash, 0.3 parts of CMC, and 0.3 parts of microcrystalline cellulose. The nickel content in the welding core is 99.3wt%.
[0067] In this embodiment, the preparation method of the composite steel core nickel-iron welding rod is as follows: cut the steel strip to the required width and roll it into a U shape using a rolling mill; place the welding core inside the U-shaped steel strip, and sew the U-shaped composite steel core with the welding core into a circle, and draw to obtain the composite steel core; sieve the components of the coating separately and weigh them according to the above ratio to obtain the coating powder; add the coating powder to a blender, and add a binder to the blender, stir and mix evenly to obtain a coating mixed powder; press the coating mixed powder onto the composite steel core, and dry it at 285°C for 1.5 hours to obtain a composite steel core nickel-iron welding rod.
[0068] In this embodiment, the weight of the welding core is 47% of the weight of the composite steel core, the weight of the composite steel core is 57% of the total weight of the welding rod, the amount of binder added is 21% of the total weight of the coating powder, and the diameter of the composite steel core is 5 mm.
[0069] Example 5
[0070] The composite steel core nickel-iron welding rod of this embodiment includes a welding core, a steel strip and a coating, wherein the welding core is wrapped inside the steel strip and the coating is coated outside the steel strip. The coating includes the following components and the weight proportions of each component are: 32 parts of marble, 18 parts of fluorite, 15 parts of barium carbonate, 5 parts of iron powder, 7 parts of graphite, 10 parts of nickel powder, 1 part of metallic manganese, 3 parts of atomized ferrosilicon, 2 parts of feldspar, 0.5 parts of soda ash, 0.3 parts of CMC, and 0.5 parts of microcrystalline cellulose. The nickel content in the welding core is 99.3wt%.
[0071] In this embodiment, the preparation method of the composite steel core nickel-iron welding rod is as follows: cut the steel strip to the required width and roll it into a U shape using a rolling mill; place the welding core inside the U-shaped steel strip, sew the U-shaped composite steel core with the welding core into a circle, and draw to obtain the composite steel core; sieve the components of the coating separately and weigh them according to the above ratio to obtain the coating powder; add the coating powder to a blender, and add a binder to the blender, stir and mix evenly to obtain a coating mixed powder; press the coating mixed powder onto the composite steel core, and dry it at 300°C for 1 hour to obtain a composite steel core nickel-iron welding rod.
[0072] In this embodiment, the weight of the welding core is 53% of the weight of the composite steel core, the weight of the composite steel core is 55% of the total weight of the welding rod, the amount of binder added is 23% of the total weight of the coating powder, and the diameter of the composite steel core is 3.0 mm.
[0073] Comparative Example 1
[0074] The nickel-iron alloy welding rod of the comparative example comprises a welding core and a coating coated on the surface of the nickel-iron alloy, wherein the welding core is made of nickel-iron alloy, and the nickel content in the nickel-iron alloy is 55wt% and the iron content is 45wt% in terms of the mass percentage of the nickel-iron alloy; the coating comprises the following components and the weight proportion of each component is: 32 parts of marble, 18 parts of fluorite, 15 parts of barium carbonate, 5 parts of iron powder, 7 parts of graphite, 10 parts of nickel powder, 1 part of metallic manganese, 3 parts of atomized ferrosilicon, 2 parts of feldspar, 0.5 parts of soda ash, 0.3 parts of CMC, and 0.5 parts of microcrystalline cellulose.
[0075] The preparation method of the nickel-iron alloy welding rod in this comparative example is as follows: sieve the components of the coating separately and weigh them according to the above ratio to obtain coating powder; add the coating powder into a blender, and add a binder into the blender, stir and mix evenly to obtain a coating mixed powder; press-coat the coating mixed powder on the nickel-iron alloy, and dry at 300°C for 1h to obtain the nickel-iron alloy welding rod.
[0076] In this comparative example, the weight of the welding core is 55% of the weight of the nickel-iron alloy welding rod, the amount of the binder added is 23% of the total weight of the coating powder, and the diameter of the nickel-iron alloy is 4.0 mm.
[0077] Comparative Example 2
[0078] The difference between this comparative example and comparative example 1 is that the diameter of the nickel-iron alloy is 3.2 mm.
[0079] Comparative Example 3
[0080] The difference between this comparative example and comparative example 1 is that the diameter of the nickel-iron alloy is 2.5 mm.
[0081] Comparative Example 4
[0082] The difference between this comparative example and comparative example 1 is that the diameter of the nickel-iron alloy is 5.0 mm.
[0083] Welding tests were conducted on the welding rods prepared in Examples 1 to 5 and Comparative Examples 1 to 4, and the welding process performance is shown in Table 1. According to "Cast Iron Welding Rods and Welding Wires (GB / T 10044-2006)", the chemical composition of the deposited metal was tested to compare the uniformity of the chemical composition of the deposited metal, and the tensile strength of the deposited metal was tested. The chemical composition of the deposited metal is shown in Table 2, and the mechanical properties of the deposited metal are shown in Table 3:
[0084] Table 1: Welding process performance of welding rods prepared in Examples 1 to 5 and Comparative Examples
[0085]
[0086] Note: The electrode utilization rate is the ratio of the length of the usable electrode to the total length of the electrode.
[0087] When the composite steel core nickel-iron welding rod of the present invention is welded, the processability of the entire welding rod does not change significantly, the spatter is small, the arc is stable, and the welding rod does not have an obvious red tail phenomenon. When the nickel-iron alloy welding rod prepared in the comparative example is welded, the welding processability of the first half is good, and after the rear section of the welding rod emits red light, the spatter becomes larger, the arc is unstable, and the processability is poor.
[0088] Table 2: Chemical composition of deposited metal and tensile strength of deposited metal of welding rods prepared in Examples 1 to 5
[0089]
[0090] The composite steel core nickel-iron welding rod of the present application wraps a steel strip around the outside of the welding core, and coats the outside of the steel strip with a coating. The welding core is made of metal nickel, and the steel strip is made of low-carbon steel. The resistivity of low-carbon steel is low, and the expansion phenomenon is not obvious. The welding rod does not have the problem of reddening and heating during welding, and the coating does not have the problem of cracking or falling off. It can achieve ultra-large current and efficient welding, reducing waste. At the same time, the welding processability and mechanical properties of the welding rod of the present application are stable. Due to the improvement of the conductivity of the welding rod, the welding rod burns more stably, the molten droplet transition is more uniform and stable, and the weld performance is more stable. Therefore, the present invention effectively overcomes some practical problems in the prior art and has a high utilization value and use significance.
[0091] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A composite steel core nickel-iron welding rod, characterized in that: The invention comprises a welding core, a steel strip and a coating, wherein the steel strip is wrapped around the outside of the welding core, the coating is coated on the outside of the steel strip, the coating comprises the following components and the weight proportion of each component is respectively: 32-40 parts of marble, 18-23 parts of fluorite, 10-15 parts of barium carbonate, 5-10 parts of iron powder, 4-7 parts of graphite, 3-10 parts of nickel powder, 1-3 parts of metallic manganese, 3-5 parts of atomized ferrosilicon, 2-4 parts of feldspar, 0.5-1 part of soda ash, 0.3-0.5 part of CMC and 0.3-0.8 part of microcrystalline cellulose; in terms of the mass percentage of the welding core, the welding core comprises the following components and the content of each component is: the nickel content is ≥99wt%, and the balance is unavoidable impurities.
2. The composite steel core nickel-iron welding rod according to claim 1, characterized in that: The steel strip is a low-carbon steel strip, and comprises the following components and the weight percentage of each component is respectively: C≤0.05%, Mn≤0.35%, Si≤0.1%, S≤0.03%, P≤0.03%, and the rest is Fe and unavoidable impurities.
3. The composite steel core nickel-iron welding rod according to claim 1, characterized in that: The weight of the welding core is 45-55% of the total weight of the welding core and the steel strip.
4. The composite steel core nickel-iron welding rod according to claim 1, characterized in that: The weight of the welding core and the steel strip is 50-60% of the total weight of the composite steel core nickel-iron welding rod.
5. A method for preparing the composite steel core nickel-iron welding rod according to any one of claims 1 to 4, characterized in that: The following steps are involved: Cut the steel strip to the required width and roll it into a U-shape using a rolling mill; The welding core is placed inside the U-shaped steel strip, the U-shaped composite steel core with the welding core is joined into a circle, and the composite steel core is drawn to obtain the composite steel core; The components of the drug coating are sieved and weighed respectively to obtain drug coating powder; Add the coating powder into a mixer, add a binder into the mixer, and stir and mix evenly to obtain a coating mixed powder; The coating mixed powder is pressed onto the composite steel core, and after drying, a composite steel core nickel-iron welding rod is obtained.
6. The preparation method according to claim 5, characterized in that: The binder is water glass binder, and the added amount of the binder is 21-23% of the coating powder.
7. The preparation method according to claim 5, characterized in that: The diameter of the composite steel core is 2.5-5.0 mm.
8. The preparation method according to claim 5, characterized in that: Marble, fluorite, nickel powder, iron powder, metallic manganese, atomized ferrosilicon, and feldspar were sieved through a 40-mesh sieve, microcrystalline cellulose was sieved through a 120-mesh sieve, and barium carbonate and soda ash were sieved through an 80-mesh sieve.
9. The preparation method according to claim 5, characterized in that: The drying temperature is 280-300°C and the drying time is 1-2h.
Citation Information
Patent Citations
LNG structure and inverse proportion formula high-alkalinity slag-system nickel-based welding rod for welding marine 9 nickel steel
CN104907729A
ENi6620 nickel-based welding rod for alternating current and preparation method and welding method thereof
CN113414519A
Coated welding rod as well as coating and preparation method thereof
CN115781107A
Stainless steel welding rod and preparation method thereof
CN115890060A
Efficient composite steel core stainless steel welding rod and preparation method thereof
CN117506228A
Cited By
Alkaline welding material with high arc stability and high impact absorbing energy and preparation method thereof
CN121892920A